Integrating Ethnobotany, Phytochemistry, and Pharmacology of Cotinus coggygria and Toxicodendron vernicifluum: What Predictions can be Made for the European Smoketree? - Antal, Diana Simona; Ardelean, Florina; Jijie, Robert; Pinzaru, Iulia; Soica, Codruta; Dehelean, Cristina (Frontiers in Pharmacology, 2021)
The smoketree (Cotinus coggygria) is a historically known medicinal plant from Southeast Europe. Its ethnomedicinal use in skin and mucosal lesions is commonly accepted across countries. Other utilizations reported locally include fever reduction, cardiac diseases, hypertension, urinary diseases, cough, asthma, hemorrhoids, diabetes, numbness of arm, liver disease, and cancer. Departing from the smoketree’s traditional uses, this review summarizes investigations on the phytochemistry and bioactivity of the plant. In vitro and in vivo experiments supporting wound-healing, anti-inflammatory, antibacterial, cytotoxic, antioxidative, hepatoprotective, and antidiabetic effects are presented. Metabolites from smoketree that are responsible for the main pharmacological effects of smoketree are pointed out. Furthermore, the review performs a comparison between C. coggygria and the lacquer tree (Toxicodendron vernicifluum). The latter is a comprehensively studied species used in Asian phytotherapy, with whom the European smoketree shares a consistent pool of secondary metabolites. The comparative approach aims to open new perspectives in the research of smoketree and anticipates an optimized use of C. coggygria in therapy. It also points out the relevance of a chemosystematic approach in the field of medicinal plants research.